Superstructure approach to the synthesis of mass exchange networks for batch processes - Mondejar, Lalilen C. (College of Engineering, University of the Philippines Diliman, 2015)
Synthesis of mass exchange networks for continuous process using different approaches and methods have been thoroughly examined in previous researches. However, studies on the synthesis of mass exchange network for batch processes are few in comparison. This study presents a method of synthesizing mass exchange networks using a superstructure approach while employing the hybrid Nelder-Mead simplex search and particle swarm optimization algorithm. The method presented in this study is applied to the mass exchanger networks in batch processes with single component and multicomponent mass transfer. This study also minimizes the capital cost of mass exchangers by including the number of trays of the mass exchangers in the objective function. In the synthesis method, the problem was divided into sub-interval. In each time interval, a simplified superstructure is constructed based on the streams present. Objective functions for each interval are also formulated and corresponding optimized designs are obtained for all the intervals. The results for all intervals are used to form the over-all optimum design for the problem. Case study was also presented to demonstrate the improved optimization method. The method introduced in this study yields better results compared to the latest established synthesis method.